2002
DOI: 10.1210/endo.143.4.8716
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of New Selective Somatostatin Receptor Subtype-2 (sst2) Antagonists, BIM-23627 and BIM-23454. Effects of BIM-23627 on GH Release in Anesthetized Male Rats after Short-Term High-Dose Dexamethasone Treatment

Abstract: We here report a pharmacological characterization of two new somatostatin (SS) receptor subtype-2 (sst2) selective antagonists by evaluating their GH-releasing activity when administered, by different routes, in anesthetized adult rats and in freely moving 10-d-old rats. Moreover, we describe the effect of these SS antagonists on the GH response to GHRH after short-term high-dose dexamethasone (DEX) treatment in young male rats. BIM-23454 and BIM-23627, given iv, were able to counteract the SS-induced inhibiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(21 citation statements)
references
References 24 publications
0
21
0
Order By: Relevance
“…In contrast, moderate SSTR5-selective agonists were effective at lowering insulin secretion, with the EC 50 of 0.2 and 1.0 nm (14) that are comparable to our data. However, the limitations of the study by Zambre et al were a moderate selectivity and the lack of evaluation of other SSTR-selective agonists (29,30).…”
Section: Discussionmentioning
confidence: 96%
“…In contrast, moderate SSTR5-selective agonists were effective at lowering insulin secretion, with the EC 50 of 0.2 and 1.0 nm (14) that are comparable to our data. However, the limitations of the study by Zambre et al were a moderate selectivity and the lack of evaluation of other SSTR-selective agonists (29,30).…”
Section: Discussionmentioning
confidence: 96%
“…Each experimental point represents the mean ± SEM of four replicate animals. When no error bars are illustrated, the SEM is smaller than the height occupied by the symbol representing the mean GC administration on GH secretion are mediated by increased SS tone [1,5]. Synthetic GHS appear to stimulate GH release, in part, through inhibition of SS pathway [3,4]; indeed, GHRP-6 is able to completely counteract glucocorticoid-mediated GH-inhibition in the rat [8].…”
Section: Discussionmentioning
confidence: 96%
“…Numerous studies have demonstrated that rats and normal men have reduced growth hormone (GH) response to GHRH and other GH secretagogues after chronic administration of pharmacological doses of GCs [3,4]. The inhibitory effects of long-term GC administration on both GH secretion and somatic growth have been demonstrated to be related to the enhancement of somatostatin (SS) hypothalamic release [1,5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the role of endogeneous SRIF as an important mediator of sexual dimorphism of GH secretion is undisputed. Additional studies with a somatostatin antagonist (21) in humans might be helpful to further investigate the neuroendocrine balance involved in the sexual dimorphism of the somatotrophic axis. Traditionally, conclusions about the potential involvement of SRIF in the regulation of GH pulsatility in humans were inferred from the classical model of Plotsky and Vale (4) obtained in male rats.…”
Section: Discussionmentioning
confidence: 99%